Optimization of Green Open Space-Based Tourism Object Development : Case Study of Panatapan Panyabungan Park in Mandailing Natal - Rahmad Suryadi Hutabarat; Cut Nuraini; Abdi Sugiarto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the factors influencing the optimization of green open space (GOS)-based tourism object development at Panatapan Panyabungan Park, Mandailing Natal Regency. This area possesses high ecological and visual potential, yet its management remains suboptimal in terms of facilities, community participation, and institutional support. The study employs a mixed methods approach, combining quantitative methods using multiple linear regression analysis on 150 respondents, and qualitative methods through in-depth interviews with key informants. The results show that simul-taneously, the four independent variables—GOS quality (X1), tourism facilities and infrastructure (X2), community participation (X3), and local government support (X4)—significantly influence the optimization of tourism development (Y). However, partially, only X2 has a significant positive effect, while X1 and X3 have significant negative effects, and X4 has no significant effect. Qualitative findings reveal that the community is not involved in decision-making, and the local government has not demonstrated concrete intervention in managing the area. These findings suggest that the strategy for developing GOS-based tourism objects should emphasize improving basic facilities, establishing participatory governance, and strengthening the structural role of local governments. A collaborative and community-based approach is key to realizing a sustainable tourism area in environmental, social, and economic aspects.